Reproductive biology of Hepatus pudibundus (Crustacea: Brachyura), the most abundant crab on the southeastern Brazilian coast - Aparecida de Lima, Paloma [UNESP]; Bertini, Giovana [UNESP]; Fransozo, Vivian; Gregati, Rafael Augusto; Correa Fernandes-Goes, Lissandra; Leao Castilho, Antonio [UNESP] (Versita, 2014)
This study analyzed the size at sexual maturity and reproductive period of populations of Hepatus pudibundus in three bays on the northern coast of So Paulo, Brazil. Crabs were collected monthly and the bottom-water temperature was measured at each collection point. The animals were sexed, measured for carapace width (CW), and their gonadal stages were determined. A total of 8,674 specimens were collected (2,435 males and 6,239 females). Adult males showed the highest mean CW; the size at maturity for both sexes was 32.5 mm CW. Reproduction was continuous and peaked in spring and summer, because of the greater availability of plankton food for the larvae. This pattern is typical in tropical and subtropical regions, unlike the seasonal reproduction found in temperate regions. Reproductive activity of females was not significantly correlated with bottom-water temperatures. Immatures and individuals in all stages of gonadal development were found throughout the sampling period and at all depths, probably because the species completes its entire reproductive cycle in that area.
Keywords: crab; breeding season; bycatch; gonadal development; sexual maturity